Lived Experiences of Secondary School Technology Leaders With Flexible Learning Environments - Bennett, Matthew (Auckland University of Technology, 2019)
Flexible Learning Environments (FLEs) are a highly topical aspect of New Zealand education due to the work of the OECD (2015) and the prioritisation of the flexible spaces by the New Zealand Ministry of Education. Much of the literature focuses generically on the characteristics of and potential for space. In addition, much of the literature is centred on primary contexts due to the integrated nature of the curriculum within these types of school. It is only in very recent times that any sort of post occupancy evaluation has occurred and it was the intention of this study to contribute towards that through the lived experiences of secondary school Technology leaders. The study describes the impact of the introduction of Technology in the New Zealand Curriculum (Ministry of Education, 1995). This is portrayed against a backdrop of curriculum design theory whereby socially constructed learning is posited against the concept of powerful knowledge as portrayed by Young and Muller (2014). The third element of the space and educational futures triangle is that of pedagogy and its relationship to space. This is addressed initially from the perspective of the failed open plan movement of the 1970s, before reframing the environment as an enabler of particular pedagogical types. The research centred on the premise that within Technology, space has been used flexibly for some time. This was due to the natural alignment between the subject and the 7+3 Framework (OECD, 2015). This allowed for the subject area to be better placed in engaging with FLEs effectively. In understanding the effects of this leadership behaviours, actions and support mechanisms afforded to and provided by Technology leaders in these spaces was explored. This phenomenological study focussed on the lived realities of four Technology leaders and through semi-structured interviews, provided their experience of the flexible use of space within their context. Attention was paid to the way in which external influences impacted on practise and also the ways in which Technology Leaders had acted on these influences. Whilst Technology leaders use space in flexible ways this tends to be through the use of multiple fixed space rather than single agile spaces. This occurred due to the shift from a finite skills approach to a practical problem solving one centred on an authentic problem which is often student defined. This spatial use resulted in cultural shifts whereby teachers entered into the physical and social space of others, thus creating a deprivatised environment whereby staff also interacted with students not formally designated to them. This freedom of approach for students, afforded by teacher agency in working with and being accountable for all students created opportunities and challenges with success being determined by staff ‘buy in’ and the framing of these conditions by the leader. Recommendations derived from the research centred on the interplay of space and the actors within it. Simply using space to drive pedagogical change is ineffective and learns nothing from the failed open plan movement. Likewise, inherently linking pedagogy to curriculum type is limiting and has contributed to the negative rhetoric towards FLEs centred on an open plan typology when the potential is much more than that. The challenge now is to understand how the agility of space can be fostered within Technology alongside the learnings for other subject areas from the experiences within Technology.
Keywords: Technology; FLE; Middle leaders; Flexible Learning Environment; ILE; Innovative Learning Environment; Educational space; Powerful knowledge; 7+3 framework; Pedagogy; Educational leadership; Change; Agility of space; Technology education; Collaboration; Collegiality; Phenomenology; Open plan